Employment accidents coverage and the execution of union activities between an adequate guarantee and an unjustified restriction to the freedom of association - Contador Abraham, Pedro; Holgado Vargas, Leonardo (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2015)
The following research intends to bring about a critical analysis on the range of coverage provided by the chilean social security system, to protect those workers who practice their right to Freedom of Association. This analysis is focused particularly during strikes, and regards the suspensive effect related to the labor relation which is considered in the Labor Code, article 337. A revision of the administrative jurisprudence has been carried out, especially article 5 paragraph 3 pertaining law Nº 16.744, which grants coverage to those employment accidents that union leaders might suffer when doing their representation duty. From this normative sanction, it has been understood so far that no equal protection should be granted to unionized workers or members when they participate in a union movement, especially during a strike. To achieve the analysis and conclusions, the ILO Freedom of Association Convention has been considered, the pronouncing of the Committee on Freedom of Association, and also the existing compared legislation regarding the topic in some spanish-american countries.